Dynamics of X chromosome hyper-expression and inactivation in male tissues during stick insect development. - Jelisaveta Djordjevic; Patrick Tran Van; William Toubiana; Marjorie Labédan; Zoé Dumas; Jean-Marc Aury; Corinne Cruaud; Benjamin Istace; Karine Labadie; Benjamin Noel; Darren J Parker; Tanja Schwander (PLoS Genetics)
Differentiated sex chromosomes are frequently associated with major transcriptional changes: the evolution of dosage compensation (DC) to equalize gene expression between the sexes and the establishment of meiotic sex chromosome inactivation (MSCI). Our study investigates the mechanisms and developmental dynamics of dosage compensation and meiotic sex chromosome inactivation in the stick insect species T. poppense. Stick insects are characterized by XX/X0 sex determination, with an X chromosome that likely evolved prior to the diversification of insects over 450 Mya. We generated a chromosome-level genome assembly and analyzed gene expression from various tissues (brain, gut, antennae, leg, and reproductive tract) across developmental stages in both sexes. Our results show that complete dosage compensation is maintained in male somatic tissues throughout development, mediated by upregulation of the single X chromosome. Contrarily, in male reproductive tissues, dosage compensation is present only in the early nymphal stages. As males reach the 4th nymphal stage and adulthood, X-linked gene expression diminishes, coinciding with the onset of meiosis and MSCI, which involves classical silencing histone modifications. These findings reveal the dynamic regulation of X-linked gene expression in T. poppense, and suggest that reduced X-expression in insect testes is generally driven by MSCI rather than an absence of dosage compensation mechanisms. Our work provides critical insights into sex chromosome evolution and the complex interplay of dosage compensation and MSCI across tissues and developmental stages.